Ivanov O.O., Prysyazhnyuk P.M., Lutsak D.L., Burda M.J., Lutsak L.D. Restoration of equipment for woodworking. - Іванов, О. О.; Присяжнюк, П. М.; Луцак, Д. Л.; Бурда, М. Й.; Луцак, Л. Д. (Problems of Tribology, 2018)
An overview of equipment and tools for removing crust from logs was conducted, and the conditions of operation of such equipment were considered. The differences of physical properties of wood of different breeds are considered. The analysis of the operating conditions of the equipment for removing bark and branches from logs is carried out, the list of factors exposed to the working units of equipment is considered. A list of materials that restores the equipment is presented. The use of tungsten material for the restoration of the work equipment of the equipment for the removal of bark is proposed and implemented